A systematic review and meta-analysis of sacubitril-valsartan in the treatment of ventricular remodeling in patients with heart failure after acute myocardial infarction - Zhou, Xiaomin; Zhu, Hongjun; Zheng, Yawei; Tan, Xiaodong; Tong, Xinyu (Frontiers in Cardiovascular Medicine, 2022)
Objective: To systematically review the efficacy and safety of sacubitril-valsartan in the treatment of acute myocardial infarction complicated with heart failure and to observe whether it can further improve patients’ cardiac function, delay left ventricular remodeling, and reduce major adverse cardiovascular events. Methods: Electronic databases including Pubmed, Embase, the Web of Science, Cochrane Library, Scopus, CNKI, Wanfang Data and VIP were searched. The search period was from the establishment of the database to March 2022 to search for relevant controlled trials. Two investigators independently screened the literature, extracted data, and assessed the risk of bias. Revman5.3 and Stata14 software were used for statistical analysis. Results: A total of 13 studies, with 6968 patients were included. Meta-analysis results showed that sacubitril-valsartan increased left ventricular ejection fraction and decreased NT-proBNP level was better at 6 months and within 3 months of follow-up compared with the control group（P＜0.00001）, but there was no significant difference at the 12-month follow-up (P＞0.05). Sacubitril-valsartan reducing LVEDD[MD=-2.55,95%CI(-3.21,-1.88),P<0.00001], LVEDVI[MD=-3.61,95%CI(-6.82,-0.39),P=0.03], LVESVI[MD=-3.77,95%CI(-6.05,-1.49),P=0.001], and increasing the distance of the 6-minute walk test[MD=48.20,95%CI(40.31,56.09),P<0.00001] were more effective. Compared with ACEI/ARB, the use of ARNI can further reduce the total incidence of adverse cardiovascular events[RR=0.72，95%CI（0.62，0.84），P＜0.0001] and the rate of HF rehospitalization [RR=0.73，95%CI（0.61，0.86），P=0.0002] in patients with acute myocardial infarction and heart failure; there was no significant difference in the incidence of cardiac death, recurrence of myocardial infarction, and malignant arrhythmia between the experimental group and the control group (P＞0.05). In terms of the incidence of adverse reactions, the incidence of cough in ARNI was lower than that in ACEI/ARB group[RR=0.69，95%CI（0.60，0.80）,P<0.00001], but the incidence of hypotension was higher [RR=1.29，95%CI（1.18，1.41）,P<0.00001], and the adverse reactions of hyperkalemia, angioedema and renal insufficiency were not increased (P＞0.05). Conclusions: The use of sacubitril-valsartan sodium in patients with acute myocardial infarction complicated with heart failure can significantly improve cardiac function and reverse ventricular remodeling, reduce the risk of re-hospitalization for heart failure.There is no apparent adverse reaction except easy cause hypotension. Systematic Review Registration：https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022322901, PROSPERO[Identifier:CRD42022322901].